THE RISK FACTORS OF HYPERTENSION DISEASE - Linda Linda (Jurnal Kesehatan Prima, 2017)
Treatment of inappropriate hypertension will be at risk for complications such as Cerebral Vascular Accident (CVA), heart failure and others. Hypertension at puskesmas Toaya is included in the top 5 most diseases in each year. In the preliminary study found that people with hypertension routine treatment since January-July as many as 152 people. The objective of the research is to know the risk factors of hypertension disease at Community Health Center in Toaya village, Sindue distric, Donggala regency. Descriptive research method, study population is hypertension patients amounted to 152 people. Sample 34 people, sampling purposive sampling. Analysis of squaret chi data. The results showed that the age of hypertensive patients aged ≥ 50 years 20 people (58.8%), age <50 years 5 people (41.2%), male gender was 26 people (76.5%), women 8 23.5% of patients had a history of hypertension of 24 people (70.6%) there was no history of hypertension 10 people (29.4%), obese no 29 people (85.3%) obese 5 people (14, 7%), had a low risk (smoking cigarettes ≤ 10 cigarettes) amounted to 15 people (44.1%), no smoking 9 people (26.5%), low physical activity category was 23 people (67.7%) high category 1 person (2.9%). The conclusion is that the age of hypertensive patients is more ≥ 50 years old, more males, have a history of hypertension, not obesity, hypertensive patients have a lower risk of smoking cigarettes (≤ 10 cigarettes), more low category physical activity. It is suggested to Toaya Puskesmas should do counseling about risk factor and effort of prevention of hypertension and it is recommended to routinely check blood pressure.